RES curtailments in Cyprus: A review of technical constraints and solutions - Therapontos, Phivos; Tapakis, Rogiros; Aristidou, Petros; Charalambides, Alexandros G. (My University, 2025)
The increasing penetration of renewable energy sources (RES) in small, isolated power systems such as Cyprus has led to significant curtailments due to technical constraints, resulting in substantial energy losses and economic impacts. This study analyzes the drivers, trends, and mitigation strategies for RES curtailments in Cyprus, where annual curtailment rates surged from 2 % (2022) to 13 % (2024), with monthly photovoltaic (PV) curtailment exceeding 28 % during low-demand periods. System-wide constraints, particularly minimum inertia requirements and ramp rate limitations of conventional generators, dominate curtailment causes, exacerbated by Cyprus's seasonal demand variability and a 780 MW PV installed capacity. Historical data reveal a 500 % increase in high-curtailment days (≥200 MWh) from 2022 to 2024, with simulations forecasting further escalation as PV capacity approaches 1 GW by 2027. Operational procedures prioritize curtailing large-scale RES installations first, thus raising equity concerns for disproportionately affected stakeholders. Mitigation strategies evaluated include infrastructure enhancements like the 1 GW HVDC Great Sea Interconnector and retrofitting aging plants as synchronous condensers to bolster inertia, alongside operational measures such as energy storage systems (ESS)—deploying 80 MW/240 MWh batteries could reduce curtailments to 10 % by 2025. Demand-side flexibility, particularly elastic electric vehicle charging, and AI-enhanced forecasting are identified as cost-effective supplements. However, reducing the minimum stable generation level (MSGL) to accommodate higher RES penetration risks frequency instability, as demonstrated by transient simulations showing critical rate of change of frequency (RoCoF) thresholds exceeding 1 Hz/s during generator outages. The study concludes that a hybrid approach combining grid reinforcement, ESS deployment, and market-driven demand response is essential to align Cyprus's RES growth with EU decarbonization targets while ensuring grid reliability.
Keywords: RES curtailments; Operational flexibility; Isolated electricity grids; Low inertia systems; Seasonal variability